Perancangan Sistem Informasi Kepegawaian Berbasis Web pada PT Bintang Selatan Agung - Lie, Valentino (JATISI, 2024)
Information systems are essential elements within organizations, supporting daily transactions and managerial functions to meet both internal and external information needs. PT Bintang Selatan Agung, a civil construction company, faces challenges such as the risk of damage and loss of physical files during recruitment, inefficiency in file retrieval, and delays in the administration of leave, promotion, demotion, termination, and punishment due to the use of manual systems. This study aims to design and implement a web-based personnel information system for PT Bintang Selatan Agung to improve the efficiency and security of employee data management. The objectives are to prevent the accumulation and damage of physical files and to expedite personnel administrative processes. The developed information system is expected to facilitate employee data management, maintain information accuracy, speed up decision-making, and enhance overall productivity and company reputation. The methodology used is the SDLC (System Development Life Cycle) with the Waterfall model. The result is a web-based personnel information system that manages recruitment, attendance, leave, promotion, demotion, transfer, reward and punishment, and termination processes. This system prevents file accumulation, reduces the risk of loss and damage, and accelerates administrative processes, thereby increasing the efficiency and effectiveness of human resource management at PT Bintang Selatan Agung.